A critical reading of the political thought of Muhammad Arkoun - mailbi, aissa (Journal of Social Sciences and Humanities, 2021)
This article aims to track the political thought of Muhammad Arkoun and explains its concepts and dismantle its terminology which it is based on . It also focuses on the sources of his political thought , which was the main base upon which his critical approach to Arab and Islamic thought was based , as he touched on the concept of political power and the meaning of supreme sovereignty then clarified the origin of both and the close relationship that binds them in Islam in order to come up with the concept of the debt of meaning which makes religion the sole controller in the lives of people. Arkoun also suggests the idea of the political connection with religion in Islam by reference to historical facts according to his own analysis and sees that there is a link made supreme sovereignty Religion has control over the conduct of political power starting from the Prophet to the period of the Rightly Guided Caliphs . According to his opinion, the authority in Islam has derived its justifications, existence, and control from the myth, but rather he states that the problem of the relationship between supreme sovereignty and political power is not specific to Islam only, but even in the West the king's authority was not recognized by the people until the church blessed it until the French Revolution came and Religious authority was abolished and established for civil authority. The solution to this problem is in the true orientation of pure secularism, which is what we touched upon in our article to finally find a critique of his political thought in terms of the concepts on which he is based, as well as the western approaches originated in his critique of Islamic political thought .